1995
DOI: 10.1093/ndt/10.supp3.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of  -tocopherol on in vitro and in vivo metabolism of low-density lipoproteins in haemodialysis patients

Abstract: It has been reported that some modified low-density lipoproteins (LDLs) such as glycated LDL and malondialdehyde-rich LDL (MDA-LDL) probably exist in the circulation. The present study was undertaken to investigate the in vitro and in vivo metabolism of MDA-LDL occurring in chronic haemodialysis patients and the effects of alpha-tocopherol on these abnormalities. MDA-LDL from haemodialysis patients was degraded more rapidly by human monocyte-derived macrophages and disappeared more slowly from the circulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 0 publications
1
12
1
Order By: Relevance
“…The lowest levels were observed in children on maintenance HD. These results are consistent with the data obtained in adult patients with CRF [28, 29]. Moreover, Taccone-Gallucci et al [30] demonstrated the beneficial effect of vitamin E supplementation by decreasing MDA in erythrocytes of uremic patients.…”
Section: Discussionsupporting
confidence: 91%
“…The lowest levels were observed in children on maintenance HD. These results are consistent with the data obtained in adult patients with CRF [28, 29]. Moreover, Taccone-Gallucci et al [30] demonstrated the beneficial effect of vitamin E supplementation by decreasing MDA in erythrocytes of uremic patients.…”
Section: Discussionsupporting
confidence: 91%
“…Supplementation of tocopherols leads to an increase of serum CEHC in both hemodialysis patients and healthy subjects and decreased CRP concentrations in hemodialysis patients (22,23). Thus, the accumulation of CEHC in hemodialysis patients may reflect anti-inflammatory functions contributing to the protective effects, which were shown in previous investigations dealing with vitamin E in hemodialysis patients (7,(24)(25)(26). Furthermore, one study by Saran et al (27) showed that antioxidant therapy with vitamin E resulted in lower ADMA levels in CKD patients, implying increased nitric oxide (NO) availability by vitamin E in renal patients.…”
Section: Discussionmentioning
confidence: 75%
“…Oxidative stress induced during HD is believed to modify LDL and produce cardiovascular complications in HD patients (26,27). However, enhanced lipid peroxidation in HD patients remains a controversial issue since many recent reports have failed to confirm the increase in plasma MDA or LOOH in these patients (28,29).…”
Section: Modification Of Ldl Into Ldlmentioning
confidence: 99%